2010
DOI: 10.1111/j.1365-2141.2010.08325.x
|View full text |Cite
|
Sign up to set email alerts
|

Advances in understanding the pulmonary infiltration in acute promyelocytic leukaemia

Abstract: SummaryIn acute promyelocytic leukaemia (APL), differentiation therapy can be complicated by the development of a differentiation syndrome (DS). Pulmonary infiltration of differentiating leukaemic cells is a key event in the development of DS. Several mediators have been identified that may promote migration and extravasation of differentiating APL cells from the bloodstream into the tissue. Adhesion of APL cells to each other and to the endothelium is induced by upregulation of the expression of adhesion mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 98 publications
(204 reference statements)
1
35
0
Order By: Relevance
“…It has been suggested that ligand-activated PML-RARA directly induces chemokine expression in differentiating APL cells, thereby triggering DS development. 9,10 Because FNDC3B-RARA is a potent transcriptional activator at pharmacological ATRA doses, it may be possible that the hyperactivated RARA signaling during ATRA therapy causes chemokine overproduction and early DS in our patient, who lacks risk factors for DS including high white blood cell counts, abnormal serum creatinine levels, and FLT3-internal tandem duplication.…”
mentioning
confidence: 99%
“…It has been suggested that ligand-activated PML-RARA directly induces chemokine expression in differentiating APL cells, thereby triggering DS development. 9,10 Because FNDC3B-RARA is a potent transcriptional activator at pharmacological ATRA doses, it may be possible that the hyperactivated RARA signaling during ATRA therapy causes chemokine overproduction and early DS in our patient, who lacks risk factors for DS including high white blood cell counts, abnormal serum creatinine levels, and FLT3-internal tandem duplication.…”
mentioning
confidence: 99%
“…In this context, IL-8, MCP-1, IL-1ÎČ and GRO-α play an important role in inducing transmigration of differentiated APL cells from blood stream into alveolar space [1,2,3,29,30]. In contrast to these studies, we studied the mechanism underlying the clearance of apoptotic APL cells during resolution phase in DS patients.…”
Section: Discussionmentioning
confidence: 90%
“…The condition can manifest as fever, oedema, hypotension, dyspnea, weight gain >5 kg and musculoskeletal pain 18,19 . The signs and symptoms together with pulmonary infiltrates often lead to the misdiagnosis of DS as pneumonia.…”
Section: Apml Differentiation Syndromementioning
confidence: 99%